PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT FOR CHILDREN WITH SPECIAL EDUCATIONAL NEEDS IN PRESCHOOL EDUCATION - Liudmyla Mashuta (Modern American Journals, 2025)
The article reveals the theoretical and methodological foundations, goals, objectives, principles and model of psychological and pedagogical support for children with special educational needs (SEN) in preschool education. The need for interdisciplinary interaction of specialists (teachers, psychologists, speech therapists, defectologists , tutors, social workers) and active partnership with the family is substantiated. The stages of support (screening and diagnostics, design of an individual educational route, implementation, monitoring and correction), key technologies (sensory integration, visual support, structured learning, elements of ABA, PECS, play and art therapy practices), as well as performance indicators are described.
Keywords: Preschool education, children with special educational needs, psychological and pedagogical support, inclusion, individual educational route, interdisciplinary team, early intervention.